Acceptance and willingness to purchase a hypothetical COVID-19 vaccine in a region under Shariah law: A cross-sectional study in Aceh, Indonesia - Muhammad A. Rayhan; Mudatsir Mudatsir; Nurjannah Nurjannah; Ichsan Ichsan; Mehrdad Amir-Behghadami; Yousef S. Khader; Ai Koyanagi; Ranjit Sah; Sandro G. Viveiros-Rosa; Mohammed A. Mamun; Yohannes K. Lemu; Assarag Bouchra; Laure SG. Linguissi; Aamer Ikram; Dina E. Sallam; Konstantinos Parperis; Uwe Wollina; Marius Rademaker; Sandro Vento; Said Usman (Narra Sains Indonesia, 2022)
Vaccines are urgently needed to control the coronavirus disease 2019 (COVID-19) pandemic. The aim of this study was to determine the acceptance of and willingness to purchase a hypothetical COVID-19 vaccine in the general population of Aceh, a holistic Shariah law implementation province in Indonesia. An online cross-sectional study was conducted using a quota sampling technique between 1 to 24 September 2021. To determine hypothetical vaccine acceptance, respondents were asked if they were willing to accept vaccines with combinations of either 50% or 95% effectiveness and either 5% or 20% risk of adverse effects. Willingness to purchase was assessed by asking whether the participants would pay for such vaccines at certain price points. Logistic regression analysis was used to assess the associated determinants. Out of 377 respondents included in the final analysis, 86.5% were willing to accept a COVID-19 vaccine with 95% effectiveness and 5% adverse effects. The acceptance rate dropped to 45.1% if the risk of adverse effects was 20%. Vaccines with 50% effectiveness and 5% adverse effects were acceptable to 42.2% but the acceptance went down to 17.2% if the risk of adverse effects increased to 20%. Multivariate analysis found that men were twice as likely to accept a vaccine with 95% effectiveness and 5% adverse effects compared to females (aOR: 2.01; 95% CI 1.05–3.86). We found that 156/377 (41.3%) of respondents were willing to purchase a COVID-19 vaccine and of these participants 71.1% were willing to pay between Indonesian Rupiah (IDR) 50,000–150,000 (US 3.33–10.00). In conclusion, the acceptance rate of a hypothetical COVID-19 vaccine varied based on effectiveness and the risk of adverse effects.